Boson Peak and Superstructural Groups in Na2O-B2O3 Glasses - Armenak A. Osipov; Leyla M. Osipova (Advances in Condensed Matter Physics)
Low-frequency Raman spectra of the sodium borate glasses with Na2O content ranging from 0 to 30 mol% were measured and analyzed from the point of view of their structure in the intermediate range order. Our results show that there is a simple linear correlation between correlation length, lc, and an average size, <R>, of the area of ordered arrangement of atoms, obtained via the distribution of the (super)structural units and their representative size. Six types of the areas of ordered arrangement of atoms were determined, being related to the presence of the B3O3⌀3 boroxol rings, B3O3⌀4- triborate rings, B5O6⌀4- pentaborate groups, B8O10⌀62- tetraborate groups, B4O5⌀42- diborate groups, and B3O63- cyclic metaborate anions in the sodium borate glasses. It was shown that the size of the areas of ordered arrangement of atoms can be determined from the simple geometric analysis of the crystallographic data on the superstructural units.